The entrepreneurial earnings puzzle: Mismeasurement or real? - Åstebro, Thomas; Chen, Jing (Journal of Business Venturing, 2014)
A review of recent evidence on relative earnings from entrepreneurship versus wage work presents a puzzle: why do individuals become entrepreneurs when entrepreneurs on average apparently earn less than employees? After considering several potential explanations, we empirically analyze one: income underreporting by entrepreneurs. Using a nationwide panel survey representing U.S. households over 15years, we estimate that entrepreneurs on average earn 4% less per year than employees. However, after correcting for income underreporting, the mean financial gain to entrepreneurship is positive and large, greater than 42%. However, we show that this estimate is built on some unpalatable model assumptions.